Nano/Micro-Structured Materials for Energy and Biomedical Applications Latest Developments, Challenges and Future Directions (Springer Singapore, 2018)
This book discusses the latest developments of the synthesis, preparation, characterization, and applications of nano/microstructure-based materials in biomedical and energetic fields. It introduces several popular approaches to fabricating these materials, including template-assisted fabrication, electrospinning of organic/inorganic hybrid materials, biomineralization-mediated self-assembly, etc. The latest results in material evaluation for targeted applications are also presented. In particular, the book highlights the latest advances and future challenges in polymer nanodielectrics for energy storage applications. As such, it offers a valuable reference guide for scholars interested in the synthesis and evaluation of nano/microstructure-based materials, as well as their biomedical and energetic applications. It also provides essential insights for graduate students and scientists pursuing research in the broad fields of composite materials, polymers, organic/inorganic hybrid materials, nano-assembly, etc.